Mathematics Learning and Teaching Directed to Process Construction - Li Yaqiong; Wenbin Xu; Xu Yiwen; Liu Bao (Research and Social Study Institute, 2020)
The Theory of Meaningful Learning shows that: to achieve the best learning effect, new knowledge should establish a non-arbitrary and substantial relationship with the existing knowledge in the learner’s cognitive structure, and the focus of the construction of the learning process is to combine the relationship between learning and teaching factors. Therefore, through the description of the application process of